Pengaruh Pembiayaan Perbankan Syariah terhadap Pertumbuhan Ekonomi: Studi Empiris di 13 Negara (Hayula: Jurnal Indonesia Studi Islam Multi-disiplin, 2018)
This study aims to analyze the effect of financing in Islamic banking on economic growth. As case studies, 13 countries are selected which covers period from 2010 to 2015 by employing the Panel GMM. The results of this study indicate that financial depth in Islamic banking has a positive influence on economic growth. In addition, this research shows that trade oppennes has a positvely contribution towards economic growth, and reversely inflation has negative impact. This research recomends policymakers to support Islamic banking industry in order to create sustainable economic development.